If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + -6 = 2(2a + -3) Reorder the terms: -6 + 5a = 2(2a + -3) Reorder the terms: -6 + 5a = 2(-3 + 2a) -6 + 5a = (-3 * 2 + 2a * 2) -6 + 5a = (-6 + 4a) Add '6' to each side of the equation. -6 + 6 + 5a = -6 + 6 + 4a Combine like terms: -6 + 6 = 0 0 + 5a = -6 + 6 + 4a 5a = -6 + 6 + 4a Combine like terms: -6 + 6 = 0 5a = 0 + 4a 5a = 4a Solving 5a = 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. 5a + -4a = 4a + -4a Combine like terms: 5a + -4a = 1a 1a = 4a + -4a Combine like terms: 4a + -4a = 0 1a = 0 Divide each side by '1'. a = 0 Simplifying a = 0
| 9x^2+10x+28=26 | | 4(2b+3)-9=11 | | m/4+5=14 | | 6x-14+3=4 | | 3x-4=4x+10 | | 6b+2=9-4b | | 3x(5-2x)=x-21 | | lgx=3 | | 6x+4y-5=0 | | k/9-1=10 | | -x^2-2x+1=0 | | x/2+7=11 | | x+(x+6)=60 | | 2(3x+1)-4=16 | | (4x^4)= | | x^3-19x^2+48=0 | | 8a-2=4a-5 | | 5n+3=2n+1 | | 2d-9=-9 | | (x-4)(x^3)= | | 10x-3=3x-1 | | 4(s+1/2)=8(s+3/4) | | t-4=-3t-10 | | 5x+16+10=47 | | 2+2y=-1+3y | | y=1.23x-0.19x^2 | | 5-7m=2-6m | | 6x-7=x-32 | | (x+6)(7x+10)=0 | | 3y^2-8y=2 | | 6-10a=8-9a | | 8-4x=18-5x |